Konstruksi elemen-elemen dasar dalam pembentukan konsep talenta kerja dalam perilaku organisasi - Fitriansyah, Fitriansyah (Faculty of Economics and Business Mulawarman University, 2016)
To complete the task or job, one must have a degree of willingness and a certain level of ability. The willingness and skills of a person is not effective enough to do something without a clear understanding of what will be done and how to do human resource performance is a combination of motivation of oneself and ability to carry out a job. This indicates that human resources can achieve satisfactory results in the work depends on the behavior of employees in carrying out the work. Talents Job (Job Talent) is the potential ability of the base and the natural person in the job which includes knowledge, skills and a series of responses that can be acquired and operated within a relatively short compared to other people, but the results of his work even more than average ability of others to be something p. The elements forming the basis of the concept of Talent Work consists of: capability above average, sustainable development, the diversity of work ability, adaptability, creativity, responsible, team development, assess the talents of others, exemplary, and reputation. The concept and basic elements forming the Talent Work can be used and / or developed further in subsequent studies to enable the improvements in science to create a new one again.Keyword: Talents Work; Organizational behavior; Performance Human Resources